Enhancement of image contrast for carbon nanotube and polymer composite film in scanning electron microscope. (2nd March 2020) - Hashimoto, Yoichiro; Ito, Hiroyuki; Sasajima, Masahiro
Abstract: Image contrast between carbon nanotubes (CNTs) and polytetrafluoroethylene (PTFE) in a CNT/PTFE composite film, which is difficult to obtain by conventional backscattered electron (BSE) imaging, was optimized to better elucidate the distribution of CNT in the film. Ultra-low landing energy condition (0.3 keV in this study) was used to prevent specimen damage due to electron beam irradiation. Signal acceptance maps, which represent the distributions of energy and take-off angle, were calculated to evaluate the features of the signal detection system used in this study. SEM images of this composite film were taken under several sets of conditions and analyzed using these acceptance maps. CNT and PTFE in the composite film can be clearly distinguished with material and topographic contrasts using the BSE signal under optimized energy and take-off angle ranges, even at ultra-low landing energy conditions.